Efektivitas Penggunaan E-Book Interaktif IPA Model PBL Terhadap Keterampilan Berpikir Kritis Peserta Didik SMP - Wahyuni, Sri; Dadan Rosana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Critical thinking skills are one of the main competencies in 21st-century learning that students, especially in science learning, must possess. However, students' critical thinking skills are still relatively low, so teaching materials are needed that can train and improve these abilities. One solution that can be applied is using interactive science e-books with the Problem-Based Learning (PBL) model. This study aims to analyze the effectiveness of interactive science e-books with the PBL model in improving students' critical thinking skills. This study uses a quantitative method with a one-group pretest-posttest Design. The research sample consisted of 30 grade VII students selected by purposive sampling. The data collection technique used a critical thinking skills test, a pretest, and a posttest with 10 descriptive questions. The data were analyzed using parametric statistics. A paired sample t-test showed a significant difference in students' average critical thinking skills after using interactive science e-books with the PBL model. The results of this study indicate that interactive science e-books with the PBL model effectively improve students' critical thinking skills. These findings indicate that using digital-based teaching materials with a PBL approach can be an innovative learning strategy for improving students' critical thinking skills in the digital era.